Model Kualitas Layanan Terbaik untuk Pelanggan di Terminal Kargo Domestik Bandara Kualanamu - Iskandar, Yelita Anggiane (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2023)
Bali Lestari Beach offers a Bali tourist experience in North Sumatra near Kualanamu Airport. Kualanamu Airport Domestic Cargo needs to improve service quality. The research developed a service quality model to increase customer satisfaction at the Kualanamu Airport Domestic Cargo Terminal with a mix-method approach. All populations are sampled for questionnaire filling. Service quality indicators are included in quadrant I model. The study involved observation, interviews, and questionnaires to determine the level of customer satisfaction at the Kualanamu Airport Domestic Cargo Terminal. Data is processed with Excel and SPSS 23. Service improvements focus on quadrant I of the Importance Performance Analysis. There are weaknesses in service quality at the Kualanamu Airport Domestic Cargo Terminal and it is recommended to focus improvements on tangibles and assurance dimensions. Based on Importance Performance Analysis, there are five selected quality improvement indicators, namely: prices are formed according to the services offered, cashiers are fast and precise in serving the payment process, employee readiness to meet every customer demand, reliability of cargo terminal equipment and facilities, and good employee treatment of service users, with good service through an effective service quality strategy.